Youth as initiators of changes in organic agricultural production in Kosovo and Metohija - Andjelka Tripkovic (BizInfo)
Recognized as an innovative concept in agriculture, organic production, due to it’s complexity, requires continuous improvement of knowledge and mastery of new skills of farmers in order to achieve numerous benefits in the long term. As organic agricultural production in Kosovo and Metohija is at the very beginning, human capital, valorized through young people, is very important for its expansive development, which in modern conditions stands out as the fourth economic pillar. The proper development of human capital in agriculture can contribute to the improvement of education about organic agricultural production, its principles, ecological sustainability, as well as the acquisition of knowledge and the development of techniques that are crucial during the management of organic crops. Considering that young farmers are the future of agriculture, especially the creative and ambitious ones, their role in this sector becomes incommensurable. This paper strives to determine, based on the conducted research, the views of young people on the importance of organic agricultural production in Kosovo and Metohija, as well as to assess the possibilities and willingness of young farmers to improve their knowledge and improve their skills in this activity.